EVOLUTION OF RELIGIOUS CAPACITY IN THE GENUS HOMO: COGNITIVE TIME SEQUENCE: with Margaret Boone Rappaport and Christopher Corbally, "Evolution of Religious Capacity in the Genus Homo: Origins and Building Blocks"; Margaret Boone Rappaport and Christopher Corbally, "Evolution of Religious Capacity in the Genus Homo: Cognitive Time Sequence"; and Margaret Boone Rappaport and Christopher Corbally, "Evolution of Religious Capacity in the Genus Homo: Trait Complexity in Action through Compassion.". Issue 1 (12th February 2018) - Rappaport, Margaret Boone; Corbally, Christopher
Abstract: Intrigued by the possible paths that the evolution of religious capacity may have taken, the authors identify a series of six major building blocks that form a foundation for religious capacity in genus Homo. Homo neanderthalensis and Homo sapiens idaltu are examined for early signs of religious capacity. Then, after an exploration of human plasticity and why it is so important, the analysis leads to a final building block that characterizes only Homo sapiens sapiens, beginning 200, 000–400, 000 years ago, when all the other cognitive and neurological underpinnings gradually came together. Because the timing of cognitive evolution has become an issue, the authors identify the time periods for these building blocks based on findings from modern cognitive science, neuroscience, genomic science, the new cognitive archaeology, and traditional stones‐and‐bones archaeology. The result is a logical, and even a likely story 55–65 million years long, which leads to the evolution of religious capacity in modern human beings.